2014
DOI: 10.1016/j.pjnns.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous phenotypic manifestations of maternally inherited deafness associated with the mitochondrial A3243G mutation. Case report

Abstract: The A3243G mutation is one of the most frequent mutations of mitochondrial DNA. The phenotypic expression of the A3243G mutation is variable and causes a wide range of syndromic and non-syndromic clinical disorders. Mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like episodes (MELAS) syndrome is the most frequent syndromic manifestation of the A3243G mutation. Stroke-like episodes seem to be the dominant feature of MELAS. We have investigated the case of a family with A3243G mutation, in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A wide range of clinical features can also present, including hearing loss, myopathy, neuropathy, migraine, epilepsy, ataxia, short stature, diabetes mellitus (DM), gastrointestinal disease, and cardiomyopathy. [ 8 9 ] Previous studies have reported a large proportion of death attributable to cardiac causes in MELAS patients. [ 7 ] Isolated MM severely affecting respiratory muscles is an uncommon clinical spectrum of m.3243A>G mitochondrial disease.…”
Section: Linical F Eaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of clinical features can also present, including hearing loss, myopathy, neuropathy, migraine, epilepsy, ataxia, short stature, diabetes mellitus (DM), gastrointestinal disease, and cardiomyopathy. [ 8 9 ] Previous studies have reported a large proportion of death attributable to cardiac causes in MELAS patients. [ 7 ] Isolated MM severely affecting respiratory muscles is an uncommon clinical spectrum of m.3243A>G mitochondrial disease.…”
Section: Linical F Eaturesmentioning
confidence: 99%
“…The first symptoms include exercise intolerance, seizures, paralysis, hemianopsia, mental anomaly, gastrointestinal disorders, respiratory muscles weakness, and arrhythmia. [ 7 8 9 ] Patients with MELAS are usually sent to the emergency room, and are predominantly initially misdiagnosed as myasthenia gravis, epilepsy, cerebral infarction, encephalitis, gastrointestinal diseases, or heart diseases, leading to mistaken treatment and delayed therapeutic opportunity. [ 1 4 7 9 ] Physicians should notice that patients are usually young.…”
Section: Ifferential D Iagnosis and mentioning
confidence: 99%
“…The decrease in ATP leads to a decrease in contractility and subsequently results in decreased stroke volume. The increase in end diastolic volume and pressure in the left ventricle causes further left ventricular remodeling, most often, left ventricular hypertrophy ( 22 ). Cardiac conductance disorders might occur by a rearrangement of the cardiac conductance system induced by the mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac conductance disorders might occur by a rearrangement of the cardiac conductance system induced by the mitochondrial dysfunction. Common cardiac conduction abnormalities seen in MIDD include Wolff Parkinson White syndrome, frequent ventricular extrasystoles, and atrial fibrillation ( 20 , 22 ). Cardiac conductance disorders might contribute to sudden deaths; therefore, patients diagnosed with MIDD should undergo a comprehensive cardiac examination to avoid adverse outcomes ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The annual and lifetime prevalence are 18% and 33% in women, respectively, and 6 and 10% in men. 24 not only the classical MELAS presentation but also MIDD (maternally inherited diabetes mellitus and deafness) 21,38,53 with or without hypertrophic cardiomyopathy and renal failure, CPEO 36,59 and mixed-phenotypes showing a variety of different complaints, signs and symptoms. 81 One explanation for the observed variation in phenotypic expression is "heteroplasmy" where wild-type mitochondrial DNA coexists with mutated molecules in the same cell and different cells have different heteroplasmy percentages.…”
Section: The M3243a>g Mutation Causes a Spectrum Of Disordersmentioning
confidence: 99%